2022
DOI: 10.3390/medicina58060760
|View full text |Cite
|
Sign up to set email alerts
|

HPV and HIV Coinfection in Women from a Southeast Region of Romania—PICOPIV Study

Abstract: Background and Objectives: Romania faces one of the highest cervical cancer burdens in Europe though it is a preventable cancer through population screening by cytology and human papillomavirus (HPV) detection. Also, it has one of the highest incidences of human immunodeficiency virus (HIV) infection. HPV and HIV coinfection are frequently encountered. The aim of study was to establish the prevalence of HPV infection among HIV-positive women in Southeast Region of Romania, to genotype high risk HPV types -and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…However, the prevalence of HPV 16 and 18 were minor at 1.44% and 1.29%, respectively, with a majority (11.35%) of HPV detected being found to be in the 'other high risk' category. This discovery is similar to that found in a Romanian study of HPV-co-infected HIV women, where the most frequent genotypes were 31 (42.1%), 56 (31.57%), and 53 (15.78%) [19]. It is a bigger challenge for such co-infected women in society who are already battling with chronic HIV disease.…”
Section: Discussionsupporting
confidence: 86%
“…However, the prevalence of HPV 16 and 18 were minor at 1.44% and 1.29%, respectively, with a majority (11.35%) of HPV detected being found to be in the 'other high risk' category. This discovery is similar to that found in a Romanian study of HPV-co-infected HIV women, where the most frequent genotypes were 31 (42.1%), 56 (31.57%), and 53 (15.78%) [19]. It is a bigger challenge for such co-infected women in society who are already battling with chronic HIV disease.…”
Section: Discussionsupporting
confidence: 86%
“…However, no correlation was identified between the HPV types and HIV viral load. Moreover, coinfection of HIV and HPV indicated that the patients are more susceptible to Candida and Gardnerella than patients without HPV 32 . The increasing (three times) susceptibility of HIV patients to HPV further indicates the concomitant infection between HIV and HPV 33,34 …”
Section: Microbial Coinfections In Hpv‐associated Cancers: An Epidemi...mentioning
confidence: 99%
“…Moreover, coinfection of HIV and HPV indicated that the patients are more susceptible to Candida and Gardnerella than patients without HPV. 32 The increasing (three times) susceptibility of HIV patients to HPV further indicates the concomitant infection between HIV and HPV. 33,34 Genital infection caused by HSV and HPV coinfections are increasingly being reported, as the lytic virus HSV-2 has the ability to modulate the barrier providing cervical mucus, leading to heightened inflammatory immune responses.…”
Section: Viral Coinfectionsmentioning
confidence: 99%
“…HIV viral load was measured using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) method using 7500 Fast Real TIME Systems (Applied Biosystems, Waltham, MA, USA) and Xpert HIV-1 Viral Load test reagents (Cepheid AB, Solna, Sweden) as described previously [8].…”
Section: Specimen Collection Hiv and CMV Serologymentioning
confidence: 99%